Adequação da metodologia de avaliação ecológica rápida para unidades de conservação marinhas - Avelar, Júlio César Lopes de (2009)
A major hindrance to the development of management Plans for sea coastal Conservation Units (CU) is the lack of information concerning marine environment, including biotic and non-biotic factors. Some reasons for that are the high costs of studies of marine environment; terrestrial environments research priority; few researchers acting in this field; lack of integration between research institutions. The Rapid Ecological Assessment (REA) consists of a flexible process to collect biological and ecological data increasingly. Through the integration of multiple levels, of informative data ecological maps that describe flora and fauna, as well as the human activities and the land use are generated. This methodology has shown efficiency at a relatively low cost data survey and systematization, and has been adopted as a basic tool for development of Management Plans development. Since this methodology was developed for terrestrial environments, it has to be adapted for marine environments. Based on The Nature Conservancy Rapid Ecological Assessment a methodology was developed to deal with data survey, systematization and analysis in order to subsidize the elaboration of marine and coastal Conservation Units Management Plan. Rapid Ecological Assessment is a planning tool and its application involves a multidisciplinary team. It begins with a macro scale analysis, using remote sensing and secondary data. This analysis is followed by field work procedures. The specific objectives of the methods are: identify, quantify and delimit the CU diverse environments; assess the environment conservation degree; identify the environmental susceptibility front to the existing threats; identify CU potentialities; establish a base of bio-ecological information and identify CU lacks of knowledge that require future research. The methodological development takes place in 9 phases, which allow the development of the following results: preliminary inventory of the CU existing fauna and flora species; inventory of the endemic, rare, threatened and exotic species; identification of possible biological indicators; identification of the real and potential threats; identification of the natural communities, their habitats and degree of conservation; map of environmental susceptibility; map of CU zoning; protection and conservation measures recommendations and CU geographic information system development